Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Baitul Maal Wal Tamwil (bmt) Nu Jombang Cabang Ngoro - Leli Akhlaqun Nisa; Siti Nur Qomariyah (Universitas Pahlawan Tuanku Tambusai, 2023)
Service quality and customer satisfaction are things that must be considered and optimized so that they can encourage customers to survive and remain the choice. Service quality is a form of customer assessment of the services provided by the company to customers. The title of this research is The Effect of Service Quality on Customer Satisfaction of Baitul Maal wal Tamwil (BMT) NU Jombang Ngoro branch. This research has a goal, namely how service quality (tangible, reliability, assurance, responsiveness, empathy) on customer satisfaction of BMT NU Jombang Ngoro branch. The test results on the t test show that tangible service quality has a partial effect on customer satisfaction with a significance value of 0.052 <0.05, reliability has a partial effect on customer satisfaction with a significance value of 0.000 <0.05, and empathy has a partial effect on customer satisfaction with a significance value of 0.011 <0.05. The results of the F test show that service quality has a simultaneous effect on customer satisfaction with a significance of 0.000 <0.05, and the results of the coefficient of determination show a contribution of 0.413 or 41.3% and the rest of the value is influenced by other aspects not tested in this study. Keywords: Service Quality, Customer Satisfactio